In vitro and in vivo evaluation of immortalized hepatocyte encapsulated click-microbeads with RGD peptide for treatment of liver failure in male rats - Win, Su Yee; Nittayacharn, Pinunta; Ngernmark, Jatupoom; Chavalitsarot, Mongkol; Thedrattanawong, Chitinart; Sa-ngiamsuntorn, Khanit; Hongeng, Suradej; Nasongkla, Norased (Frontiers in Bioengineering and Biotechnology, 2025)
Cell encapsulation in biocompatible microbeads offers a promising strategy for cell-based therapy in acute liver failure (ALF). This study evaluates the use of immortalized hepatocyte cells (imHCs) encapsulated in click-arginyl glycyl aspartic acid (click-RGD)-modified alginate microbeads, focusing on their biocompatibility and therapeutic potential. In vitro assessments showed that click-RGD microbeads significantly enhanced cell viability on day 4, spatial distribution, and hepatocyte function, evidenced by increased albumin on day 14 and alpha-fetoprotein (AFP) secretion compared to unmodified alginate microbeads. For in vivo testing, ALF was induced in Sprague-Dawley male rats using D-galactosamine (D-gal), followed by intraperitoneal administration of imHCs-loaded click-RGD microbeads in the treated group and CMRL medium injection in the control group. Treated rats exhibited faster reductions in aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels, higher albumin production, and improved liver histology, characterized by reduced necrosis and the absence of inflammation, on day 14 after treatment. No adverse host responses were observed, confirming the biocompatibility of the microbeads. These findings support the potential of click-RGD microbeads as a therapeutic platform for ALF, warranting further studies on long-term implantation, immune response, and co-encapsulation strategies.